2011
DOI: 10.1038/oby.2010.172
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Overweight and Obesity on Longitudinal Trends in Maternal Serum Leptin Levels During Pregnancy

Abstract: Maternal obesity influences a number of metabolic factors that can affect the course of pregnancy. Among these factors, leptin plays an important role in energy metabolism and fetal development during pregnancy. Our objective was to estimate the influence of maternal overweight/obesity on variation in the maternal serum leptin profile during pregnancy. In a prospective cohort of 143 adult gravidas with singleton pregnancies presenting for general prenatal care, we measured serum leptin levels at 6–10, 10–14, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 25 publications
(45 reference statements)
9
78
1
2
Order By: Relevance
“…Several studies have shown that weight gain during pregnancy is lower in obese than in non-obese women. 37,44,90,91 It is possible that non-pregnant obese women have a chronic increase of inflammatory mediators, and during pregnancy, these do not increase so much because the placental production of these factors is lower than that of adipose tissue. More research is needed to establish the clinical utility of these inflammatory molecules in the management of obese pregnant women.…”
Section: Main Implications For Practicementioning
confidence: 99%
“…Several studies have shown that weight gain during pregnancy is lower in obese than in non-obese women. 37,44,90,91 It is possible that non-pregnant obese women have a chronic increase of inflammatory mediators, and during pregnancy, these do not increase so much because the placental production of these factors is lower than that of adipose tissue. More research is needed to establish the clinical utility of these inflammatory molecules in the management of obese pregnant women.…”
Section: Main Implications For Practicementioning
confidence: 99%
“…Experimental and clinical investigations have shown that maternal obesity during pregnancy increases the risk of the offspring developing obesity (29,39,42). Obesity is characterized by elevated levels of leptin in both nonpregnant and pregnant females (23,30,33). The adipocyte cytokine leptin plays a key role in energy homeostasis regulation (22), and circulating leptin levels are proportional to the body adipose mass (13).…”
mentioning
confidence: 99%
“…На метаболиче-ские нарушения, связанные с дисфункцией адипоцитов в жи-ровой ткани у женщин с ожирением, может повлиять уровень лептина во время беременности. Исследование Misra [29] было первым, четко продемонстрировавшим, что избыточная масса тела/ожирение женщин до беременности определяют качественно иной профиль лептина в течение беременности, по сравнению с беременными без избытка массы тела/ожире-ния. Избыток массы тела и ожирение авторы определили ин-дексом массы тела >26,0 кг/м 2 .…”
Section: гормоны жировой ткани при материнском ожиренииunclassified